Church and power in De ecclesiastica potestate of Aegidius Romanus - Roche Arnas, Pedro (Anales del Seminario de Historia de la Filosofía, 2007)
Every legitimate exercise of political power owes its very existence to Church. On the other hand, every Church power lies in papal power. Therefore, the power of the Pope himself, even in earthy matters, is a total, absolute power, sine pondere, numero et mensura, as Egidio points out. Two powers, two swords but just a unique authority: that of the Pope.